PENGARUH CORPORATE TAX RATE, NON DEBT TAX SHIELD, PROFITABILITY DAN OPERATING LEVERAGE TERHADAP TINGKAT HUTANG PERUSAHAAN-PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) ANTARA TAHUN 2011-2013 (Students' Journal of Accounting and Banking, 2015)
This study aims to examine and analyze the influence of corporate tax rate, non dept tax shield, profitability and operating leverage of the debt level manufatur companies listed in Indonesia Stock Exchange (BEI) between 2011-2013. The sample in this study as many as 228 companies selected by purposive sampling technique Manufacturing Company listed on the Stock Exchange 2011-2013. But after doing outlier sample to 223 companies. Data analysis was performed using multiple linear regression. The results showed that the Corporate Tax Rate and Profitability significantly negative effect, Non Dept Tax shield positive effect was not significant and Operating Leverage negative effect was not significant on Debt Levels.Keywords: Level of Debt, Corporate Tax Rate, Non-Debt Tax Shield, Profitability and Operating Leverage